Analisis Kesulitan Belajar Membaca Permulaan pada Peserta didik Kelas I Sekolah Dasar di Batusangkar - -, Ratmiati (el-Ibtidaiy:Journal of Primary Education, 2023)
The main problem in this study is the lack of students' initial reading ability, so it is necessary to analyze the difficulties that affect students' initial reading ability. This study aims to determine students' learning difficulties in beginning reading. This type of research is a qualitative descriptive research. The subjects of this research were the first grade students of elementary school 23, Rambatan, Batusangkar. There are also data collection tools in this study in the form of observation, interviews and documentation. While the data that has been collected is then analyzed using descriptive qualitative data analysis techniques, namely data reduction, data presentation and drawing conclusions (verification). The results of this study are first, there are students who are not fluent in reading because students have not been able to recognize letters or words globally. students have not been able to understand sound symbols, students do not understand the relationship between letters and sounds in words including knowledge of all letters (consonants, vowels, double consonants, dead sounds, perfect sounds, and so on). fourth,. second, students have difficulty in stringing letters into syllables, third, students have difficulty in assembling syllables into words and students reduce/eliminate some letters.